1990
DOI: 10.1080/00288233.1990.10428469
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Argentine stem weevil,Listronotus bonariensis(Kuschel), populations in pasture: the egg stage

Abstract: Sampling systems for the egg stage of the Argentinestem weevil,Listronotus bonariensis (Kuschel), are briefly reviewed. Sampling techniquesdeveloped and extensivelytestedby the authors are described.Taylor's power law analysis was performed on sample mean-variance relationships for eggs per tiller and tillers per soil core. These were used to develop numerical sampling equations. A sampling plan is described for sampling populations of eggs to attain specific levels of precision at differentpopulationdensities. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…L. bonariensis prepares to oviposit by chewing a hole in the leaf sheath of a tiller and then via the hole, insert eggs between the upper and lower epidermis of the leaf sheath. When the larvae hatch they typically bore into the tiller and move downwards toward the base (Barker and Addison, 1990 ). This study has shown that L. bonariensis oviposition was significantly lower on native grasses compared with hybrid ryegrass.…”
Section: Discussionmentioning
confidence: 99%
“…L. bonariensis prepares to oviposit by chewing a hole in the leaf sheath of a tiller and then via the hole, insert eggs between the upper and lower epidermis of the leaf sheath. When the larvae hatch they typically bore into the tiller and move downwards toward the base (Barker and Addison, 1990 ). This study has shown that L. bonariensis oviposition was significantly lower on native grasses compared with hybrid ryegrass.…”
Section: Discussionmentioning
confidence: 99%
“…To convert eggs counts per 200 tillers, the number of eggs per square meter was calculated from tiller counts on 50 turf plugs, each 50 mm in diameter. These sampling techniques provided estimates of L. bonariensis egg and grass tillers populations with standard errors Ͻ15% of the means (Barker and Addison 1990). The frequency of N. lolii infection in ryegrass was determined each autumn and spring by microscopical examination (400ϫ magniÞcation) of sheath tissues from 50 randomly selected ryegrass tillers that had been stained in heated lactophenol-aniline blue.…”
Section: Methodsmentioning
confidence: 99%
“…Sampling of infested grassland using sweep nets after dark, when adults are feeding, can provide good estimates of population size, as can direct soil sampling (May, ; Barker and Addison, ; Proffitt et al., ). Sticky traps can be used to capture flying adults (Goldson et al., ).…”
Section: Pest Categorisationmentioning
confidence: 99%